New association of milk thistle and artichoke extracts enhances egg quality in caged-laying hens - Serra, Valentina; Leone, Francesca; Harper, Valeria; Fiorini, Lorenzo; Del Zozzo, Francesca; Chabrillat, Thibaut; Carlu, Claire; Archetti, Ivonne Laura; Pastorelli, Grazia; Tedesco, Doriana Eurosia Angela; Guerrini, Alessandro (Frontiers in Veterinary Science, 2025)
IntroductionEgg quality is crucial to productivity and laying hens’ health. However, hens’ aging, oxidative stress, and metabolic disorders (e.g., liver steatosis) can impair egg production and quality during the production cycle. Nutritional interventions may help preserve productivity under these conditions. Among plant extracts, milk thistle (Silybum marianum L.) and artichoke (Cynara scolymus L.) are noteworthy for their bioactive compounds with hepatoprotective and antioxidant properties. This study evaluated the effectiveness of a combined extract of milk thistle and artichoke (PHYTO-LAYER™), standardized in silibinin (2.4 g/L) and chlorogenic acid (2.2 g/L), in maintaining or improving egg quality, lipid oxidation, and antioxidant capacity in caged-laying hens exposed to hepatic and metabolic stress.MethodsA total of 792 Lohmann LSL-White hens (41 weeks old) were randomly assigned to two groups, control and treated (396 hens per group). The treated group received the products via drinking water at a dose of 1 mL/L, intermittently for 7 weeks (7 consecutive days every 2 weeks). Sampling occurred at five time points (T0–T5). At T0, T3, and T5, 60 eggs per group were collected for quality indices evaluation, while 13 hens per group were sampled for serum biochemical investigations.ResultsPHYTO-LAYER™ improved egg, yolk, and albumen weight (p < 0.000), eggshell thickness (p < 0.000), and the total polyphenol content (p < 0.026), with an enhancement of yolk antioxidant capacity (p < 0.024). However, the Haugh unit of treated eggs was reduced (p < 0.000).DiscussionEgg quality often deteriorates during late production stages due to oxidative stress and hens’ aging. Given the antioxidant potential of silibinin and chlorogenic acid, their combined intermittent administration supports and maintains the egg quality in caged-laying hens exposed to metabolic stress and after the peak of production. However, further studies could be of interest to verify whether similar changes in egg-quality indices are observed with other phytoextract administration protocols, such as continuous administration, and at different administered doses.